As formas de tratamento de segunda pessoa do singular em cartas do seridó potiguar - Sousa, Gisonaldo Arcanjo de (2019)
Based on the variational sociolinguistics, led by Labov (2008 [1972], 1994, 2003), among others, I aim to analyze the variation among the second person personal pronouns of the singular TU, YOU and THE LADY in the subject function of personal letters produced in the 1940s by four individuals from the Seridó region of Rio Grande do Norte.I analyze the variation between the pronouns TU, VOCÊ and A SENHORA in the second person singular indication in the role of subject. I use data extracted from personal letters written between 1941 and 1944 by four natural individuals from Seridó, Rio Grande do Norte. I take into account two social factors, the sex and the age of the writers, and two discursive-pragmatic factors, the social relations and the subject. Based on the analysis of all these factors, Brown and Gilman (1960) propose that the choice of forms of treatment is conditioned by relations of power and solidarity among the interlocutors. Among the main results, I point out that the distribution of pronouns in terms of sex and age did not bring clear indications of a shift towards increasing use of VOCÊ, the most recent form. There was exclusive use of A SENHORA in the ascending asymmetrical relation of the son-mother and the variable use of TU and VOCÊ in the other social relations. In the asymmetric mother-son relationship, VOCÊ were much more frequent, and in the symmetrical girlfriend-boyfriend relationship, TU was much more frequent. There was greater balance in the distribution of the data in the symmetrical friend-friend relationship, with a predominance of VOCÊ. Finally, regarding the subject, TU was more frequent in topics of an intimate nature. The results allowed to frame the distribution of the pronouns in the first of the three stages of the historical development of the VOCÊ proposed by Lopes et al. (2018), characterized by a higher frequency of TU, especially in intimate relationships.